Edukasi Hukum Bagi Komunitas Pemuda Pulau Barrang Caddi sebagai Upaya Peningkatan Kesadaran Hukum dalam Pengelolaan Wilayah Pesisir - Muh. Ikhsan Idrus; Umar Iskandar; Hasyrif S Y; Suprianto Suprianto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service Program (PKM) aimed to improve legal literacy among coastal communities in Barrang Caddi Island, Makassar, particularly regarding spatial planning regulations, the protection of customary rights, and the legal implications of coastal development. The program was conducted on May 17, 2025, involving community leaders, local authorities, fishermen, and youth representatives. A normative-empirical approach was applied, combining regulatory review, field observation, interviews, and participatory legal education. The results indicate that legal literacy in the community remains low due to limited access to legal information, insufficient previous outreach, and weak institutional capacity. However, the legal education activities proved effective in enhancing participants’ understanding of their rights, encouraging active participation in discussions, and fostering initiatives to engage in coastal spatial planning advocacy. The program recommends the implementation of continuous, community-based legal education supported by government institutions, universities, and law enforcement agencies to strengthen the protection of coastal communities’ rights and promote sustainable development in Indonesia’s coastal areas